The defeat of the left in Ecuador in the extractivism-ecology cleavage - Álvaro Ramón Sánchez (2022)
Poverty and climate change are the main global challenges of the 21st century and also two interconnected problems. In the second half of the 20th century, new cleavages appeared, such as feminism, multiculturalism, and environmentalism, along with the social class division. The climate crisis creates the developmentalism-environmentalism dimension, which overlaps the classic distinction between left and right, and can be represented in a double ideological axis. The political debate between development and sustainability has advanced in Latin America with respect to other places due to its dependence on extractivism and its biodiversity. The impacts of extractivism have led to the appearance of two criticisms considered to be leftist but with different economic and political strategies and incompatible in many aspects: neo-extractivism and post-extractivism. In the Latin American context at the beginning of the 21st century, the relationship between neo-extractivism and eco-indigenism is complex. The conditions of possibility for the breakup of the progressive bloc are developing throughout the region, but they are especially intense in Ecuador. The division has become visible in the 2021 presidential election, in which the left-wing sweeps in the first round but surprisingly loses in the second one, showing that Ecuador’s politics are incomprehensible without adding the extractivism – post-extractivism dimension. The double ideological axis is an analysis method adaptable to the political systems of more and more countries. In addition, it is not a static tool, but its positions can be altered by political events such as the articulation of a right-wing environmentalism in Ecuador and in some European countries.